Phenotypic and genetic characteristics of Streptococcus mutans isolates from site-specific dental plaque in China - Liu, Shanshan; Li, Huihui; Zhang, Kai; Guo, Zhenfei; Zheng, Qingwei; Hu, Fuyong; Zhang, Wei; Sun, Yu; Guan, Jun-chang (Journal of medical microbiology, 2021)
Introduction. Streptococcus mutans is an important cariogenic microbe. Hypothesis/Gap Statement. The potential characteristics of S. mutans isolates from site-specific dental plaque are still not clear. Aim. This study aimed to investigate the phenotypic and genetic characteristics of S. mutans isolates from site-specific dental plaque in China. Methodology. We used S. mutans isolated from children with early-childhood caries (ECC) and caries-free children to compare the phenotypic and genetic characteristics of S. mutans from site-specific dental plaque samples. The ECC subjects presented two sites: a cavitated lesion and a sound surface. The caries-free subjects presented one sound surface. Growth pattern, biofilm, decrease in pH, extracellular polysaccharide, expression levels of virulence-related genes, multilocus sequence typing (MLST) and phylogenetic trees were evaluated among these three sites. Results. The phenotypes detected between the cavitated and sound surfaces of ECC children were similar. However, the capacity for biofilm formation, pH drop and expression levels of genes ( gtfB and spaP ) of S. mutans in the caries-free group were lower compared with those of the ECC group. We identified 44 new alleles and 77 new sequence types. More than 90 % of the children with ECC shared an identical sequence type. The distribution of sequence types among different subjects showed diversity, and child-to-child transmission was detected. Conclusions. This is the first report of MLST on site-specific dental plaques in a single subject, and indicates that S. mutans isolated from site-specific dental plaque of a single subject showed similar phenotypes as a result of the isolates were closely related.